Nutritional Properties of Rice Varieties Commonly Consumed in Italy and Applicability in Gluten Free Diet - Vici, Giorgia (Foods, 2021)
Gluten-free diets are often characterized by an inadequate intake of nutrients and are generally monotonous for the limited number of products celiac patients can use. As rice is the most used cereal by celiac consumers, studying rice varieties nutritional characteristics is of interest to manage diet quality and variety. Proteins, total carbohydrates and amylose content of six rice varieties (Ribe, Vialone Nano, Carnaroli, Arborio, Basmati, and Fragrance) were analyzed. Analyses were performed in raw products and after boiling, stewing, and microwaving. A decrease of proteins and total carbohydrates amount was observed in cooked rice. The same was reported for amylose content with boiling showing the highest loss (average retained amylose 53%). Considering amylose percentage with respect to total carbohydrates, each variety showed either an increase or a decrease depending on cooking method. The highest values were obtained with stewing above all for Basmati rice and Arborio rice. However, exceptions can be underlined as Carnaroli rice, showing the highest percentage when boiled. In this context, nutritional characteristics of cooked rice varieties appear to be of great importance to increase specific nutritional knowledge to better manage gluten-free diets.